Analisis Peningkatan Pendapatan Usaha Tani Sayur Masyarakat Di Desa Parhorboan,Kecamatan Pagaran - Tupa Pebrianti Lumbantoruan; Ibelala Gea (Jurnal Mahasiswa Kreatif, 2024)
Green vegetables is a term in Indonesian that refers to types of vegetables that have a green color. In general, green vegetables contain various important nutrients such as fiber, vitamins and minerals which are beneficial for health. Various types of green vegetables include leaves, leafy vegetables, and other green plants that are usually cooked as part of everyday meals,product. various journals, books and scientific sourcesas well as with Mr. Harryono Aritonang as a vegetable farmer in Parhorboan Village, Kec. Pagaran, Kab. North Tapanuli has experienced price increases in recent times, on November 6 2023, the price of vegetables, including green mustard greens, white mustard greens and other mustard greens, reached around 10,000/kg Previously the price which was IDR 5,000/kg the previous two. This increase in vegetable prices occurred due to weather events that were not good or adequate,Parhorboan Village is due to the quality getting better.